Wykorzystanie internetu w podnoszeniu konkurencyjności MŚP na przykładzie wybranych firm województwa podkarpackiego - Ichniowska, Agnieszka; Wiażewicz, Joanna (Role of Internet in the Increase of Small and Medium Enterprises Competitiveness on the Example of the Selected Firms from Podkarpackie Providence, 2006)
Small and medium size enterprises put a big effort to use information in the process of their development. There are many possibilities of getting information, but Internet has become one of the most important source, also for Polish enterprises. The paper is about small and medium enterprises that run their businesses in the region of Podkarpacie. Its goal is to show how big meaning and influence has Internet on SME and how many ways are available for entrepreneurs to use it. There are also some examples of using Internet by SME in Podkarpacie.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 418-425